The distribution and retention of paclitaxel and doxorubicin in multicellular layer cultures - Lee, Joo Ho; Na, Kun; Song, Soo-Chang; Lee, Jaehwi; Kuh, Hyo-Jeong (SPANDIDOS PUBL LTD, 2012)
Limited distribution of anticancer drugs has been recognized as a significant hurdle to efficacy. We investigated a detailed penetration/distribution profile of paclitaxel-rhodamine (PTX-rd) and doxorubicin (DOX) in multicellular layer (MCL) cultures of human cancer cells as an in vitro model for avascular regions of solid tumors. MCLs were exposed to drugs and fluorescent images of frozen sections were acquired for determination of drug penetration into MCL under various exposure conditions. PTX-rd and DOX showed drastically different profiles of penetration. DOX showed full penetration after I h and accumulation over 3 h, whereas PTX-rd showed slow and limited penetration, with accumulation only within the top 20% of layers by 2 h and insignificant penetration even at 72 h. Drug retention in MCL was more dependent on drug concentration, rather than exposure time, i.e., drug distribution increased by 6.3- and 2.5-fold for PTX-rd and DOX, respectively, when exposed to higher concentrations under comparable AUC exposure (1 mu M x 24 h vs. 50 mu M x 0.5 h). Anti-proliferative activity of PTX and DOX in MCL, as determined by cell cycle analysis, was minimal and may be attributed, at least in part, to their limited distribution in multicellular cultures. Overall, we demonstrated that penetration and retention of PTX and DOX in MCL was not only concentration- and time-dependent, but also schedule-dependent. It is suggested that slow releasing formulations or a slow infusion regimen may not necessarily be desirable, especially for PTX, due to insufficient penetration and accumulation which may result from a low local concentration at the target site.
Keywords: SOLID TUMORS; ANTICANCER DRUGS; EXTRAVASCULAR TRANSPORT; P-GLYCOPROTEIN; LIMITED PENETRATION; TISSUE PENETRATION; DNA INTERCALATOR; RESISTANCE; SPHEROIDS; MODEL